White-coat hypertension and normotension in the League of Hypertension of the Hospital das Clínicas, FMUSP: prevalence, clinical and demographic characteristics - Segre,Carlos A. (2003)
OBJECTIVE: To assess the prevalence of white-coat normortension, white-coat hypertension, and white-coat effect. METHODS: We assessed 670 medical records of patients from the League of Hypertension of the Hospital das Clínicas of the Medical School of the University of São Paulo. White-coat hypertension (blood pressure at the medical office: mean of 3 measurements with the oscillometric device ³140 or ³90 mmHg, or both, and ambulatory blood pressure monitoring mean during wakefulness < 135/85) and white-coat normotension (office blood pressure < 140/90 and blood pressure during wakefulness on ambulatory blood pressure monitoring ³ 135/85) were analyzed in 183 patients taking no medication. The white-coat effect (difference between office and ambulatory blood pressure > 20 mmHg for systolic and 10 mmHg for diastolic) was analyzed in 487 patients on treatment, 374 of whom underwent multivariate analysis to identify the variables that better explain the white-coat effect. RESULTS: Prevalence of white-coat normotension was 12%, prevalence of white-coat hypertension was 20%, and prevalence of the white-coat effect was 27%. A significant correlation (p<0.05) was observed between white-coat hypertension and familial history of hypertension, and between the white-coat effect and sex, severity of the office diastolic blood pressure, and thickness of left ventricular posterior wall. CONCLUSION: White-coat hypertension, white-coat normotension, and white-coat effect should be considered in the diagnosis of hypertension.